The Effect of the Use of Civics Teaching Aids Media on Students' Understanding - Laila, Nurul; Hariyani, Yunita; Firmansyah, Ihwan (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aims to investigate the impact of using visual aids on students' understanding of Civics in Class V at UPTD SD Negeri Patenteng 4, Modung District. The research adopts a quantitative approach and includes all fifth-grade students at UPTD SD Negeri Patenteng 4 as the population, totaling 16 students, consisting of 7 female and 9 male students. The study is conducted at UPTD SD Negeri Patenteng 4, Modung District. Data collection techniques involve observation, tests, questionnaires, and documentation. The data is analyzed through validity testing, reliability testing, normality testing, and paired simple T-Test. The results of the hypothesis analysis indicate that the student's learning outcomes improved after utilizing visual aids in the learning process. The average pre-test score was 68.13, while the average post-test score was 85.88, suggesting a significant increase in learning outcomes. The statistical analysis in IMB SPSS v21.0 revealed a significance value of 0.000, indicating that using visual aids significantly impacts student understanding, facilitating their mastery of the subject matter and enhancing the meaningfulness of the learning process.